AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS EKSTRAK KULIT KAYU RARU (COTYLELOBIUM SP.) - Gunawan Pasaribu; Titiek Setyawati (Jurnal Penelitian Hasil Hutan, 2025)
Research on natural medicinal plants has been growing due to the increasing interest to natural medicinal material that is considered safer than synthetic medicines. In North Sumatera, bark of Cotylelobium sp which is locally known as raru, bas been widely utilized by the local community. The skin bark of this species is commonly used as a mixture of "nira" to produce "tuak" (Batak's traditional alcoholic liquor). In addition, local community has been using this species for traditional bealing as well. This research is to study the potency of raru's skin bark in producing anticocidant using DPHH method. The taxicity activity of the material was also examined using Brine Shrimp Lethality Test (BSLT) method. Results show that the yield extract of Cotylelobium melanocylon Pierre was 30.11% and Cotylelobium lanceolatum Craib was 14.50%. Both extracts contains flavonoid, tanin, saponin, triterpenoid and bidroquinon. The extract of Cotylelobium melanocylon Pierre has antioxidant activity against DPPH radical with value of IG as mus as 108.487 ppm and 77.909 ppm for Cotylelobium lanceolatum Craib. Furthermore, the toxicity of Cotylelobium melanoxylon Pierre was 643.550 ppm and Cotylelobium lanceolatum Craib was 767.191 ppm LC